2021
DOI: 10.1111/1462-2920.15833
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia in scale insects: a distinct pattern of infection frequencies and potential transfer routes via ant associates

Abstract: Wolbachia is one of the most successful endosymbiotic bacteria of arthropods. Known as the 'master of manipulation', Wolbachia can induce a wide range of phenotypes in its host that can have farreaching ecological and evolutionary consequences and may be exploited for disease and pest control. However, our knowledge of Wolbachia's distribution and the infection rate is unevenly distributed across arthropod groups such as scale insects. We fitted a distribution of within-species prevalence of Wolbachia to our d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 122 publications
0
6
1
Order By: Relevance
“…In a previous study, a positive correlation between Wolbachia infection in scale insects and their associates indicated that ants may play a role in host‐shifting (Sanaei, Lin, et al, 2021). Here, we found that only one out of five cases of infected ant–scale insect pairs shares the same Wolbachia strain (Table S2, Figure S4).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In a previous study, a positive correlation between Wolbachia infection in scale insects and their associates indicated that ants may play a role in host‐shifting (Sanaei, Lin, et al, 2021). Here, we found that only one out of five cases of infected ant–scale insect pairs shares the same Wolbachia strain (Table S2, Figure S4).…”
Section: Discussionmentioning
confidence: 95%
“…In a previous study, we screened 689 scale insect specimens for Wolbachia (Sanaei, Lin, et al, 2021). Among samples with positive Wolbachia infection, we selected those whose multilocus sequence typing (MLST) genes (Baldo et al, 2006) were successfully amplified.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the horizontal transmission of endosymbionts via the parasitoids of insects represents a potential pathway. Besides parasitoid wasps, ants are also known to harbour Wolbachia (Keller et In the study of scale insects and their associated groups (ants, wasps, beetles, ies, mites, moths, and thrips), Sanaei et al (2021) showed that signi cant differences in Wolbachia infection rates in the scale insects were found in ant attendance and the associated groups but wasps, suggesting a possible route of horizontal transfer between ants and scale insects. Nonetheless, it is unlikely that Wolbachia was transported by ants into Tuberculatus aphids because the two nonattended species, T. higuchii A-and B-types, showed over 10% infection rates and a mean infection rate of 30% in ant-attended species seems to be a low score considering constant contact with ants.…”
Section: Discussionmentioning
confidence: 99%